2018
DOI: 10.1007/s10897-018-0245-5
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Issues Surrounding Clinical Exome Sequencing in the Prenatal Setting

Abstract: Exome sequencing is a clinical diagnostic test offered primarily for children and adults with suspected genetic conditions. The purpose of this study was to explore issues related to exome sequencing in a reproductive clinical setting. This was a qualitative study using semi-structured interviews. Participants were professionals drawn from four key stakeholder groups-healthcare providers, laboratory/industry, ethics, and government. Transcribed interviews were analyzed for emergent themes. Most participants sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 44 publications
1
26
0
1
Order By: Relevance
“…7 In particular, prior studies have identified the conflict between respect for patient autonomy and the potential harms of uncertainty and unquantifiable risk, ultimately resulting in outcomes that are discordant with robustly autonomous medical decision making. 29 Prior studies have suggested that use of evidence-based counseling methods, guidelines on most applicable clinical scenarios for trio-ES, and standardization of reporting of results may improve patient autonomy in decision making 27 Our study has many strengths. It is a large, prospective cohort with longitudinal data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 In particular, prior studies have identified the conflict between respect for patient autonomy and the potential harms of uncertainty and unquantifiable risk, ultimately resulting in outcomes that are discordant with robustly autonomous medical decision making. 29 Prior studies have suggested that use of evidence-based counseling methods, guidelines on most applicable clinical scenarios for trio-ES, and standardization of reporting of results may improve patient autonomy in decision making 27 Our study has many strengths. It is a large, prospective cohort with longitudinal data.…”
Section: Discussionmentioning
confidence: 99%
“…The issues surrounding pre and post-test counseling, including interpretation of results and potential patient harms associated with anxiety, uncertainty, and missed parental expectations are in line with previously noted challenges of incorporating trio-ES into the prenatal fold. 27 28 Previous work from our group discussed specific examples of ethical counseling challenges that have risen from this ongoing prospective cohort, identifying the importance of effective and appropriate communication of uncertainty and how it may impact long-term parental decisions. 7 In particular, prior studies have identified the conflict between respect for patient autonomy and the potential harms of uncertainty and unquantifiable risk, ultimately resulting in outcomes that are discordant with robustly autonomous medical decision making.…”
Section: Discussionmentioning
confidence: 99%
“…A body of evidence has been published over recent years looking at healthcare professionals (HPs) experiences and attitudes towards returning uncertain results following prenatal CMA, and more recently ES. These studies have been conducted in countries including the Netherlands, 12 United States of America (USA), 13–15 United Kingdom (UK), 16–18 Hong Kong 19 and Australia 20,21 . The findings have highlighted differences in opinions and practice both across and within countries, regarding the management of uncertain results 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Surveys of clinicians and parents have reported that most believe that pES will have clinical utility related to diagnosing genetic conditions, impacting pregnancy management, facilitating decisions about pregnancy termination, preparing for childhoodonset conditions, and informing reproductive planning. 22,24,[30][31][32][33] In stark contrast, a study of 14 US health-care insurance payers reported that none believed that decisions about TOP, withdrawal of intensive care, provision of palliative care, family planning, or directing families to disease-specific resources (e.g., support groups, research) were aspects of clinical utility of pES, and only a minority agreed that referral to a tertiary center for specialized care was an aspect of clinical utility. 28 Therefore, it will be challenging to reconcile the different perspectives of the various pES stakeholders to establish its clinical utility.…”
Section: Discussionmentioning
confidence: 99%
“…21 Most genetics providers believe that pES will have clinical utility. [22][23][24][25] Previous studies of pES indicate that results can impact decision-making about continuation or termination, pre-or postnatal medical management, delivery planning, recurrence risk counseling, reproductive planning, and parental medical management. [8][9][10]13,18,20,26 However, there are also risks and limitations of pES that must be considered.…”
Section: Introductionmentioning
confidence: 99%